2015
DOI: 10.1084/jem.20142384
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant actin depolymerization triggers the pyrin inflammasome and autoinflammatory disease that is dependent on IL-18, not IL-1β

Abstract: Kim et al. identify an autoinflammatory disease in mice that is driven by IL-18, resulting from an inactivating mutation in the actin-depolymerizing cofactor Wdr1. This alteration in actin dynamics is recognized by the pyrin inflammasome and results in exaggerated monocyte IL-18 production, whereas inflammasome activation in mature macrophages is unaltered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 53 publications
(77 reference statements)
5
75
0
Order By: Relevance
“…A recent report suggests that an inactivating mutation in WDR1, an actin-depolymerizing cofactor, induces Pyrin-dependent IL-18 secretion and drives an autoinflammatory disease in mice (25). This observation supports the postulate that Pyrin functions by sensing a signaling event downstream of Rho modification/ inactivation in the actin cytoskeleton pathway (22).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…A recent report suggests that an inactivating mutation in WDR1, an actin-depolymerizing cofactor, induces Pyrin-dependent IL-18 secretion and drives an autoinflammatory disease in mice (25). This observation supports the postulate that Pyrin functions by sensing a signaling event downstream of Rho modification/ inactivation in the actin cytoskeleton pathway (22).…”
supporting
confidence: 60%
“…Thus, the microtubule network possibly serves as a platform for a conformational change in Pyrin and subsequent ASC recruitment following toxin-induced dephosphorylation. The Pyrin inflammasome responds to Rho-inactivating toxins (22,23) and also to an inactivating mutation in WDR1 (25), both of which cause depolymerization of the actin filaments. Thus, Pyrin may function to monitor the proper dynamics of the actin cytoskeleton and particularly pathological disruptions of the actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of Pyrin inflammasome activation has also been recently studied in Wdr1 rd/rd mice that are homozygous for a hypomorphic allele of Wrd1, a protein, which is required for disassembly of actin filaments [149]. Wdr1 rd/rd mice exhibit spontaneous autoinflammatory manifestations that are dependent on IL-18R, but not IL-1R1 signaling.…”
Section: Excessive Il-1b and Il-18 Productionmentioning
confidence: 99%
“…The third group comprises the tripartite motif (TRIM) family member pyrin. It was recently shown that F-actin induces assembly of pyrin [15]. After sensing the inducer directly or indirectly, the sensors undergo conformational change, interact with, and induce polymerization of, the adaptor protein ASC (apoptosis-associated speck-like protein with a CARD) in a prion-like fashion via PYD-PYD interactions.…”
Section: Role Of Inflammasomes In the Activation Of Caspase-1mentioning
confidence: 99%
“…However, this is not the only inflammasome activated by the virus. Furthermore, NLRP3 is also activated in P2RX7-independent fashions [12,15,16]. In addition to NRTIs, several HIV protease inhibitor (PIs) like indinavir and nelfinavir inhibit maturation of prelamin A, required for the assembly and integrity of nuclear membranes [111].…”
Section: Il-18/il-18bp Imbalance In Hiv Infectionmentioning
confidence: 99%